A novel HLA-B allele, HLA-B*35:279, identified by sequencing-based typing in a Czech patient - Mrazek, F; Onderkova, J; Königova, N; Siffnerova, V; Vrana, M; Ambruzova, Z; Skoumalova, I; Petrek, M; Raida, L (International journal of immunogenetics, 2016)
The identification of a novel HLA-B*35:279 allele in a Czech patient is described. This allele is identical to the B*35:03:01 variant except the G/A nucleotide exchange at position 652 of the HLA-B gene that corresponds to the amino acid substitution from valine to isoleucine in alpha 3 domain of the HLA-B antigen.
Keywords: Histocompatibility Testing; alely; HLA-B Antigens; testování histokompatibility; Amino Acid Substitution; Alleles; Humans; sekvence nukleotidů; Česká republika; Base Sequence; substituce aminokyselin; lidé; HLA-B antigeny; Czech Republic